Sulfur and Oxygen Isotopic Composition of Dissolved Sulfate in Interstitial Water Sample Residues from IODP Site U1553 on the southern Campbell Plateau - Alex Reis; Vanessa Fichtner; Andrea M Erhardt (PANGAEA, 2023)
Dissolved sulfate sulfur and oxygen isotope results and carbonate associated sulfate sulfur isotope results from IODP Site U1553 (166°11.4801'E, 52°13.4294'S) located on the Campbell Plateau are presented. Pore water collected during IODP Expedition 378 at Site U1553 in January 2020 were used for this study. These samples were processed using a procedure modified from that in Wotte et al. (2012, doi:10.1016/j.gca.2012.02.013) to extract the sulfate from the aqueous phase. The dissolved sulfate in the pore water was extracted by first adding 10% HCl to acidify the pore water, then the sulfate was removed from solution as barium sulfate using a 10% BaCl2 solution. Sulfur isotopes in dissolved sulfate were analyzed using an EA-Isolink elemental analyzer connected in continuous flow to a MAT253 IRMS and the oxygen isotopes in dissolved sulfate were measured using a thermal conversion elemental analyzer connected in continuous flow to a Delta V IRMS. Analytical precision was measured using repeated measurements of a blind standard with an average 2-sigma of 0.4 extperthousand for sulfur isotopes (IAEA-SO-5) and 0.3 extperthousand for oxygen isotopes (NBS-127). These data were collected to examine the impact of a long-duration (~26-million-year) unconformity has on the fidelity of the carbonate geochemical archive.